Learning in Educational Computer Games for Novices: The Impact of Support Provision Types on Virtual Presence, Cognitive Load, and Learning Outcomes - Schrader, Claudia; Bastiaens, Theo (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
Embedding support devices in educational computer games has been asserted to positively affect learning outcomes. However, there is only limited direct empirical evidence on which design variations of support provision influence learning. In order to better understand the impact of support design on novices’ learning, the current study investigates how support devices and their type of provision (intrinsic vs. extrinsic) determine games’ effectiveness on learning outcomes. This effectiveness is also related to how the design-type of provision influences learners’ virtual presence and cognitive load. Compared to an educational adventure game without additional support, the results indicate that the game equipped with support devices enhances learning outcomes, although no differences in cognitive load were found. A variation in the design of provision shows no effect. In order to gain a more thorough understanding of support devices and their design for games, additional learner characteristics (e.g., interest) should be considered in future research.